2021
DOI: 10.3390/rs13040656
|View full text |Cite
|
Sign up to set email alerts
|

Using UAV LiDAR to Extract Vegetation Parameters of Inner Mongolian Grassland

Abstract: The accurate estimation of grassland vegetation parameters at a high spatial resolution is important for the sustainable management of grassland areas. Unmanned aerial vehicle (UAV) light detection and ranging (LiDAR) sensors with a single laser beam emission capability can rapidly detect grassland vegetation parameters, such as canopy height, fractional vegetation coverage (FVC) and aboveground biomass (AGB). However, there have been few reports on the ability to detect grassland vegetation parameters based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…It occurs because UAV-derived CH data, unlike point-wise manually measured ones, represent a mean plant height value of an entire plot accounting for the plant density resulting from zonal statistics. Another solution to provide CH data for reliably estimating crop traits might be utilizing UAV-LiDAR data [71][72][73] and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs because UAV-derived CH data, unlike point-wise manually measured ones, represent a mean plant height value of an entire plot accounting for the plant density resulting from zonal statistics. Another solution to provide CH data for reliably estimating crop traits might be utilizing UAV-LiDAR data [71][72][73] and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Guimarães-Steinicke et al [81] regarded mean height and LAI as metrics of vertical structure, community stand gaps, canopy surface variation and emergent flowers as metrics of horizontal structure. Airborne or UAV-based LiDAR data could also be attempted to estimate the canopy structure characteristics of grassland over large areas [82]. However, the detection of grassland structure remains a challenge compared with forests, due to the more complex canopy structure and the smaller size of individual plants.…”
Section: Methods For Grassland Species Diversity Estimationmentioning
confidence: 99%
“…The overall payload of the UAV ranges from 2.5 kg to 6.0 kg, with a maximum payload of 50 kg [23,[27][28][29][30][31]. The flight altitude of UAVs varies from 10 to 100 meters, and some scholars have studied the impact of flight altitude on modelling accuracy [32,33].…”
Section: Uav Platforms and Sensorsmentioning
confidence: 99%
“…For example, Wang et al studied the application ability of UAV LiDAR technology in modelling canopy height and coverage of grassland and used the extracted average canopy height, maximum canopy height and FVC to estimate the AGB [33]. The research results of Zhang et al in Hulunbuir, Inner Mongolia, also showed that UAV LiDAR data could effectively estimate the canopy height, FVC and other parameters of grasslands, and grassland AGB could be retrieved with higher accuracy through multiparameter joint inversion [32].…”
Section: Vegetation Parameter Inversionmentioning
confidence: 99%